Economic analysis of surgical treatment of hip fracture in older adults - Fabiano Bolpato Loures; Alfredo Chaoubah; Valdeci Manoel de Oliveira; Alessandra Maciel Almeida; Estela Márcia de Saraiva Campos; Elenir Pereira de Paiva (Universidade de São Paulo, 2015)
OBJECTIVE To analyze the incremental cost-utility ratio for the surgical treatment of hip fracture in older patients. METHODS This was a retrospective cohort study of a systematic sample of patients who underwent surgery for hip fracture at a central hospital of a macro-region in the state of Minas Gerais, Southeastern Brazil between January 1, 2009 and December 31, 2011. A decision tree creation was analyzed considering the direct medical costs. The study followed the healthcare provider's perspective and had a one-year time horizon. Effectiveness was measured by the time elapsed between trauma and surgery after dividing the patients into early and late surgery groups. The utility was obtained in a cross-sectional and indirect manner using the EuroQOL 5 Dimensions generic questionnaire transformed into cardinal numbers using the national regulations established by the Center for the Development and Regional Planning of the State of Minas Gerais. The sample included 110 patients, 27 of whom were allocated in the early surgery group and 83 in the late surgery group. The groups were stratified by age, gender, type of fracture, type of surgery, and anesthetic risk. RESULTS The direct medical cost presented a statistically significant increase among patients in the late surgery group (p < 0.005), mainly because of ward costs (p < 0.001). In-hospital mortality was higher in the late surgery group (7.4% versus 16.9%). The decision tree demonstrated the dominance of the early surgery strategy over the late surgery strategy: R$9,854.34 (USD4,387.17) versus R$26,754.56 (USD11,911.03) per quality-adjusted life year. The sensitivity test with extreme values proved the robustness of the results. CONCLUSIONS After controlling for confounding variables, the strategy of early surgery for hip fracture in the older adults was proven to be dominant, because it presented a lower cost and better results than late surgery.